2018
DOI: 10.1063/1.5027473
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field-induced crossover from the inverse Faraday effect to the optical orientation in EuTe

Abstract: A time-resolved optical pump-probe technique has been applied for studying the ultrafast dynamics in the magnetic semiconductor EuTe near the absorption band gap. We show that application of external magnetic field up to 6 T results in crossover from the inverse Faraday effect taking place on the femtosecond time scale to the optical orientation phenomenon with an evolution in the picosecond time domain. We propose a model which includes both these processes possessing different spectral and temporal propertie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…We note that a sharp peak at zero delay time can be a consequence of the IFE and understood in terms of the third-order optical nonlinearity χ (3) ( ω ; ω , −ω , ω ) when pump and probe beams overlap. 42…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that a sharp peak at zero delay time can be a consequence of the IFE and understood in terms of the third-order optical nonlinearity χ (3) ( ω ; ω , −ω , ω ) when pump and probe beams overlap. 42…”
Section: Resultsmentioning
confidence: 99%
“…We note that a sharp peak at zero delay time can be a consequence of the IFE and understood in terms of the third-order optical nonlinearity χ (3) (ω; ω, −ω, ω) when pump and probe beams overlap. 42 Fig. 3a and b show the magnetization dynamics for EuO and Eu(Gd)O at different temperatures.…”
Section: Pump-probe Measurementsmentioning
confidence: 99%
“…4 c reveals a difference between the measured and modelled value of the initial phase ϕ 0 . This indicates secondary, non-damping-based excitation mechanisms, such as an optical spin transfer torque 35 , 36 or optical orientation 37 , which could become relevant because of the smallness of α in YMnO 3 as compared to HoMnO 3 . These mechanisms, which are based on absorption rather than spin damping, involve an angular momentum transfer from the circularly polarised pump pulse to the material.…”
Section: Resultsmentioning
confidence: 99%
“…Previous experiments on undoped EuO showed that the static conductivity was increased by the irradiation of continuous laser beam [34] and the dynamic enhancement of magnetization by ultrashort laser pulses was possible as demonstrated by means of time-resolved Faraday rotation [35]. In addition, it has been reported that the spin orientation can be controlled by circularly polarized optical pulses via the inverse Faraday effect in EuO [36] and EuTe [37], and the ultrafast dynamics and modulation of the exchange interaction can be accessed using an all-optical technique in EuTe [38]. In this study, ultrafast spin dynamics after the photoexcitation were investigated in carrier-density-controlled ferromagnetic semiconductor Eu 1−x Gd x O films by using a pump-probe nonlinear magneto-optical spectroscopy [39][40][41][42] (Figure 4a), as described below.…”
Section: Methodsmentioning
confidence: 99%